2020
DOI: 10.3892/etm.2020.9438
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF‑β1‑mediated epithelial‑mesenchymal transition in the pathogenesis of tympanosclerosis

Abstract: The present study aimed to explore the role of TGF-β1-mediated epithelial-mesenchymal transition (EMT) in the pathogenesis of tympanosclerosis. Sprague Dawley rats were injected with inactivated Streptococcus pneumoniae suspension to establish a rat model of tympanosclerosis. The rats were sacrificed 8 weeks after the model was established. H&E and von Kossa staining was used to observe the morphological changes of middle ear mucosa. Western blotting was used to detect the expression of TGF-β1 and EMT-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Oil-infused silicone also greatly limited the deposition of fibronectin (fig. S15), which is associated with the TM inflammatory response that can lead to biofilm formation, myringitis, and rejection of the device ( 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Oil-infused silicone also greatly limited the deposition of fibronectin (fig. S15), which is associated with the TM inflammatory response that can lead to biofilm formation, myringitis, and rejection of the device ( 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest S. lutetiensis promoted ccRCC development, but the underlying mechanisms were unclear. Previous studies reported that some Streptococcus species activated TGF -β signaling in various diseases, e.g., Streptococcus pneumoniae induced TGF -β1 expression during tympanosclerosis pathogenesis ( Qiu et al, 2021 ), asthma inflammation ( Schmit et al, 2020 ) and pulmonary infection ( Peteranderl et al, 2017 ). So we theorized that S. lutetiensis promoted ccRCC via TGF -β signaling, to explore this possibility, the ACHN cell line was co-cultured with Sl.CM or BHI and the mRNA expression levels of the TGF -β signaling pathway were assessed by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Pathologic EMT can be triggered by lymphocyte activation and secretion of transforming growth factor-beta (TGF-b). Mouse models with knockout of TGF-b show protection from fibrosis and EMT (153)(154)(155). Growth factors such as VEGF and TGF-b also mediate interactions between the lung endothelium and pericytes and have been independently studied as drivers of fibrosis (156,157).…”
Section: Airway Inflammation In the Pathogenesis Of Cladmentioning
confidence: 99%